Bilateral paraganglioma. (9th November 2012) - Trivedi, Rushikesh Yogesh; Leong, Samuel C
Abstract : A 41-year-old man presented with bilateral, painless, non-pulsatile left-sided neck swelling. This was noticed incidentally on a routine medical check-up. He had no significant medical history and did not take any regular medications. Urinary catecholamines and routine blood tests were all normal, and when he had been examined he was normotensive. The MRI scan revealed an enhancing lesion on the left side of the neck as seen in figure 1; it measured 4 cm×3 cm and had a 'salt and pepper' appearance causing splaying of the internal and external carotid arteries at the level of the bulb. There was a similar enhancing lesion on the right side, measuring 2.6 cm×2 cm at the level of the carotid bifurcation and 5 cm× 2.6 cm at the jugular bulb, this is seen in figure 1. A diagnosis of bilateral paraganglioma was made.